2017
DOI: 10.1002/chem.201702805
|View full text |Cite
|
Sign up to set email alerts
|

Highly Microporous Nitrogen‐doped Carbon Synthesized from Azine‐linked Covalent Organic Framework and its Supercapacitor Function

Abstract: Porous carbons with nitrogen-doped (N-doped) structures are promising materials for advanced energy conversion and storage applications, including supercapacitors and fuel cell catalysts. In this study, microporous N-doped carbon was successfully fabricated through carbonization of covalent organic frameworks (COFs) with an azine-linked two-dimensional molecular network (ACOF1). In the carbonized ACOF1, micropores with diameters smaller than 1 nm are selectively formed, and a high specific surface area (1596 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 42 publications
0
41
0
Order By: Relevance
“…Figure a presents the CV curves of the TPT‐DAHQ COF recorded at various scan rates, from 5 to 200 mV s −1 . The CV curves all had rectangular shapes, even when recorded at the highest scan rate of 200 mV s −1 , suggesting capacitive behavior with a high rate performance suitable for use in supercapacitors . The distinct appearance of humps in the rectangular CV curves revealed that the capacitive response was derived from a combination of electric double‐layer capacitance (EDLC) and pseudocapacitance arising from the presence of heteroatoms (i.e., nitrogen and oxygen atoms) .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Figure a presents the CV curves of the TPT‐DAHQ COF recorded at various scan rates, from 5 to 200 mV s −1 . The CV curves all had rectangular shapes, even when recorded at the highest scan rate of 200 mV s −1 , suggesting capacitive behavior with a high rate performance suitable for use in supercapacitors . The distinct appearance of humps in the rectangular CV curves revealed that the capacitive response was derived from a combination of electric double‐layer capacitance (EDLC) and pseudocapacitance arising from the presence of heteroatoms (i.e., nitrogen and oxygen atoms) .…”
Section: Figurementioning
confidence: 99%
“…Figure b provides galvanostatic charge‐discharge (GCD) curves of the TPT‐DAHQ COF recorded at various current densities, from 0.5 to 20 A g −1 . The GCD curves display triangular shapes with a slight bend, implying the existence of both EDLC and pseudocapacitance arising from heteroatoms (i.e., nitrogen and oxygen atoms) . The specific capacitance was calculated from the GCD curves using equation (S1) as shown in Figure c. The TPT‐DAHQ COF exhibited excellent specific capacitance of 256 F g −1 at current density of 0.5 A g −1 which was decreased to 131 F g −1 when the current density was increased to 20 A g −1 .…”
Section: Figurementioning
confidence: 99%
“…Kim et al prepared a microporous N-doped carbon by the direct carbonization of an azine-linked covalent organic framework (ACOF1) (Figure 24a). [100] For the carbonized ACOF1, the microporous structure was formed selectively with diameters smaller than 1 nm, and the specific surface area was as high as 1596 m 2 · g À 1 . Moreover, the carbonized ACOF1 showed a higher specific capacitance than the carbonized COF1 (Figure 24b), 234 vs 191 F · g À 1 at the current density of 1 A · g À 1 .…”
Section: Carbonized Cofs As Electrode Materialsmentioning
confidence: 99%
“…Kim et al. prepared a microporous N‐doped carbon by the direct carbonization of an azine‐linked covalent organic framework (ACOF1) (Figure a) . For the carbonized ACOF1, the microporous structure was formed selectively with diameters smaller than 1 nm, and the specific surface area was as high as 1596 m 2 ⋅ g −1 .…”
Section: Applications Of Cofs In Supercapacitorsmentioning
confidence: 99%
“…The material was composed of amorphous carbon with micropores on the shell frame and with specific surface areas as high as 525 m 2 /g. Kim et al [84] successfully synthesized microporous N-doped carbons by the direct carbonization of an azine-linked two-dimensional molecular network. The carbonized COF presented high specific surface area (1596 m 2 /g), uniform micropores (less than 1 nm), and N-doped graphitic carbon structure.…”
Section: Porous Carbon From Cofsmentioning
confidence: 99%